Seasonal variation in the allometry of wing pigmentation in adult males of the territorial damselfly Hetaerina vulnerata (Insecta Odonata). Issue 2 (3rd March 2020) - Rodríguez-Escobar, Frida E.; Carrillo-Muñoz, Aldo I.; Serrano-Meneses, Martín A.
Abstract : Several sexually selected traits exhibit positive allometry. One of the explanations for this pattern suggests that positive allometry should be expected only for "pure" threat male signals, whilst isometry and negative allometry should occur in "pure" courtship signals. Wing pigmentation (WP) is a sexually selected trait exhibited by the males of several damselfly taxa (Odonata Zygoptera), which has been the focus of a number of studies of allometry. Whilst WP tends to exhibit positive allometry in many taxa, the pattern is not general. Previous studies have shown that in Hetaerina vulnerata, a territorial species in which WP is used as a "pure" threat signal, positive allometry is common. However, little attention has been paid to the seasonal variation in the allometry of WP in this species. To address this research gap, we collected data from a full reproductive season, from a natural population of H. vulnerata located in Central Mexico. Our results suggest that, first, male WP and body size generally increase throughout the season. Second, WP increases as the end of the season approaches, independently of body size. Finally, WP tends to be either not related to body size, or to exhibit isometry during the first half of the season (April–June), and positive allometry during the second half of the season (July–October). We suggest that our results may be explained by (i) the availability of resources critical to the development of larvae, as well as the duration of development, and (ii) an increase in the number or larger males towards the end of the season, which may favour the exaggeration of WP. Furthermore, the opportunity for sexual selection may vary, so that WP may be more relevant to male mating success towards the end of the reproductive season.